Identificação de contaminação de solo em área vitícola: avaliação preliminar e investigação confirmatória - Bellé, Érica (My University, 2024)
Soil contamination by metals, resulting from successive applications of pesticides and fertilizers in viticultural áreas, affect the productivity and biodiversity of ecosystems, allowing the leaching of these substances in groundwater. Since there is a possibility that viticultural areas may be contaminated by metals because they have received pesticide and fertilizer applications for decades, this study aimed to perform the identification step proposed by the Brazilian legislation CONAMA Resolution nº 420/2009. By Preliminary Assessment and Confirmatory Investigation provided in NBR 15515/2011, parts 1 and 2, was sought to prove the existence of possible contamination and propose techniques for minimizing contaminants in a rural area of the city of Bento Gonçalves/RS. Thus, the area was evaluated considering information about its history of use through an interview with the person in charge; characteristics of the physical environment; pesticides used on the farm through consultation of record books; concentrations of the metals chromium (Cr), nickel (Ni), copper (Cu), zinc (Zn), and cadmium (Cd) through soil sampling at three points on the property (P1 between the forest and the plantation; P2 in a 50-year-old cultivated area; and P3 a 20-year-old cultivated area); and also, remediation actions were proposed for three scenarios. The analyzes were done by acidic digestion and determined via Optical Emission Spectroscopy with Inductively Coupled Plasma (ICP-OES). The results showed that the sites with potential for contamination are close to concrete tanks used for manual mixing of grouts, as well as close to sheds where grouts are currently stored, handled, and prepared to be mechanically sprayed. Soil analysis showed that the soil located in a 20-year-old cultivation area (P3) is classified as Class 3 since Ni and Cr concentrations exceed the "Prevention" values established by legislation, while the soils of the other points (P1 and P2) are classified as Class 2. The proposed scenarios contemplated: (1) actions to decrease contamination with the presence of agricultural activity, (2) mitigation and natural regeneration with the absence of agricultural activity, and finally, (3) the electrokinetic technique was indicated for remediation. The conclusion is that the soil analyzed is not contaminated, however, actions are needed to reduce the concentration of contaminants so that the values of "Investigation" and Class 4 are not reached, not compromising the environmental quality, the planting, and the health of farmers. [resumo fornecido pelo autor]
A contaminação de solo por metais, decorrente de sucessivas aplicações de agrotóxicos e fertilizantes em áreas vitícolas, afeta a produtividade e a biodiversidade dos ecossistemas além de possibilitar a lixiviação destas substâncias para as águas subterrâneas. Visto que há possibilidade de áreas vitícolas possuírem contaminação por metais, por receberem a décadas aplicações de agrotóxicos e fertilizantes, o presente estudo objetivou realizar a etapa de Identificação proposta pela Resolução CONAMA nº 420/2009. Por meio da Avaliação Preliminar e Investigação Confirmatória, dispostas na NBR 15515/2011 partes 1 e 2, buscou-se comprovar a existência de possível contaminação, e propor técnicas de minimização de contaminantes de área situada em zona rural do município de Bento Gonçalves/RS. Dessa forma, a área foi avaliada considerando informações sobre: seu histórico de uso por meio de entrevista com responsável; características do meio físico; agrotóxicos utilizados na propriedade rural por meio de consulta aos cadernos de registros de campo; concentrações dos metais de cromo (Cr), níquel (Ni), cobre (Cu), zinco (Zn) e cádmio (Cd) por meio de amostragem no solo em três pontos da propriedade (P1 entre a mata e plantio; P2 em área cultivada de 50 anos; e P3 área cultivada de 20 anos); e ainda, foram propostas ações de remediação para três cenários. As análises dos solos foram realizadas por meio da digestão ácida e determinação via Espectroscopia de Emissão Ótica com Plasma Indutivamente Acoplado (ICP-OES). Os resultados obtidos mostraram que os locais com potencial de contaminação são as proximidades de tanques de concreto utilizados para mistura manual de caldas, além de proximidades de galpões em que atualmente ocorrem o armazenamento, manejo e preparo de caldas para serem pulverizadas mecanicamente. As análises de solos mostraram que o solo localizado em área de cultivo de 20 anos (P3) se enquadra como Classe 3, visto que as concentrações de Ni e Cr ultrapassam os valores de "Prevenção" dispostos pelas legislações vigentes, já os solos dos demais pontos (P1 e P2) se enquadram como Classe 2. Os cenários propostos contemplaram: (1) ações para diminuição da contaminação com presença atividade agrícola, (2) atenuação e regeneração natural com ausência de atividade agrícola, e por fim, (3) indicou-se a técnica de eletrocinética para remediação da área. Conclui-se assim, que os solos dos pontos amostrados não estão contaminados, porém necessita-se de ações para a diminuição das concentrações de contaminantes para que os valores de "Investigação" e Classe 4 não sejam atingidos, não comprometendo a qualidade ambiental, o plantio e a saúde dos agricultores. [resumo fornecido pelo autor]
Keywords: Engenharia ambiental; Solos - Poluição; Solos - Análise; Solos - Descontaminação; Biorremediação; Fitorremediação